LABYRINTHS INTELLIGENCE - Геник, С. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
More than one hundred years ago the first test of intellect as so-called as Intellectuality Coefficient (IQ) has been created. In according to the last researches the positive correlation between the IQ and the vital success is saved only till the value 115-120. Such qualities as consciousness, officiousness, capacity and emotional intellect determine the further successes of man.